A Frontier Diocese in Search of a Patron Saint: the Promotion of the Cult to Pedro González in Tui in the 13th century - Lopes Frazão da Silva, Andréia Cristina (Madrygal. Revista de Estudios Gallegos, 2017)
The Diocese of Tui, organized in the sixth century, was dismantled by the impact of the arrival of the Muslims in the eighth century. In the middle of the ninth century it has been restored, but the tudenses bishops continued to reside in other sees. In the early eleventh century, Tui was the target of Norman incursions. The city was destroyed and his prelate taken prisoner. Thus, the diocese was aggregated to Lugo and later Iria-Santiago, a situation which lasted until about 1071. Only in the late eleventh century the tudense bishopric was definitely restored and the episcopal lordship was also established. In the following century, with the formation of the Portuguese kingdom, it became a border diocese. This location had contributed to the enrichment of the episcopate, which received donations and privileges of portuguese, castilian and leonese nobility. However, there wasn’t, until the early thirteenth century, a saint directly linked to the history of the tudense church. At the middle of 1240s, the dominican Pedro González died and was buried in the Cathedral of Tui, which, according to my hypothesis, has become the ideal candidate to be the patron of the episcopate. The purpose of this article is to discuss this hypothesis.